Innovate! : how great companies get started in terrible times - Meyer, Thomas A. (Hoboken, N. J. : John Wiley & Sons, 2010)
'Learn the lessons of how great companies began in the worst economic times--Eli Lilly, IBM, Medtronic, Procter & Gamble, Hewlett-Packard and Marvel Entertainment. All great companies and all made their start during the worst economic times. Innovate!: How Great Companies Get Started in Terrible Times is first and foremost a source of true inspiration based on history. But it goes much further than that. It captures the lessons of these great innovative individuals and companies that began in the worst economic times, identifying the philosohies, strategies, and essential keys to success during your own challenging economic times. Provides a compass to navigate troubled economic waters though innovation. Explains the creative sources of innovation possessed by every individual Harnesses the power of innovation of the individual and the organization. Innovate!: how great companies get started in terrible times shows you the strides you and your organization can take toward thriving in the worst of times. And it just might be your road map to building the next great American business success story'--
Includes bibliographical references and index.
Keywords: New business enterprises -- United States; Financial crises -- United States